The impact of social features on the financial sustainability of pension systems in Central and Eastern Europe and Baltic States - Dumiter, Florin Cornel; Schebesch, Klaus Bruno; Nicoară, Ștefania Amalia; Bențe, Cristian (Technological and Economic Development of Economy, 2024)
This paper analyses the financial sustainability of pension systems from the perspectives of labour supply, population aging, and demographic changes. The time period chosen was 1995 to 2022 and it takes into account nine countries from Central and Eastern Europe and the Baltic States. The econometric modelling techniques used are traditional linear regression, ridge and lasso regression, cross-validated glmnet models, and xboost flexible model used for the whole nine countries and also for country groups. The empirical results show that government expenditures and revenues in terms of social security funds are influenced by the demographic changes of the population that we face nowadays, are bound to the population aging phenomenon, and are dependent upon the elderly labour supply movements. The conclusions of this article reveal the practical need to reshape the financial sustainability of pension systems in all nine countries by developing a sustainable pension scheme that needs to be adjusted to the new social, demographic, and behavioural patterns of labour supply.